2017
DOI: 10.1016/j.jvscit.2017.06.003
|View full text |Cite
|
Sign up to set email alerts
|

Development of a pulsatile, tissue-based, versatile vascular surgery simulation laboratory for resident training

Abstract: Simulation in surgery is becoming an important component of surgical education. Training on bench top models has been demonstrated to improve technical skills. The objective of our project was to create a vascular surgery simulation model. The simulation model consists of a platform, artificial blood reservoir, artificial blood, inflow and outflow limbs, electric motor, battery, pulse generator, and cryopreserved vessel. Three different vascular surgery simulation stations were created: carotid endarterectomy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 9 publications
(11 reference statements)
0
13
0
Order By: Relevance
“…However, the study by Black did not conclude anything, 19) whereas in one by Fletcher et al, the efficacy of the simulator used was found to be inconclusive. 17) The mean NIH score 23) of all included studies was 7.2 (ranging from 5 to 8). According to AHRQ grading, 24) two studies were found to be of ʻpoorʼ quality, 15,17) whereas the rest of the studies were scored as ʻfairʼ or ʻgood.ʼ…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…However, the study by Black did not conclude anything, 19) whereas in one by Fletcher et al, the efficacy of the simulator used was found to be inconclusive. 17) The mean NIH score 23) of all included studies was 7.2 (ranging from 5 to 8). According to AHRQ grading, 24) two studies were found to be of ʻpoorʼ quality, 15,17) whereas the rest of the studies were scored as ʻfairʼ or ʻgood.ʼ…”
Section: Resultsmentioning
confidence: 99%
“…One of these studies describes the development of the simulation model and did not involve any subjects for model validation. 17) Eight out of 10 focused on technical skills as their major outcome. 3,5,16,[18][19][20][21]27) Two studies focused on anatomical knowledge and non-technical skills such as ʻcrisis managementʼ in addition to procedural skills.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Low cost models, advanced open simulators with lifelike pulsatile flow, animal models, and human cadavers are being used for training open procedures such as open abdominal aortic aneurysm (AAA) repair or carotid endarterectomy. 19,26 Endovascular procedures can be trained using a variety of models and simulators: glass models, advanced virtual reality simulators, anaesthetised pigs and sheep, as well as cadavers. 22,27e30 Acquisition of a simulator is only one small step to offer simulation based training, it is crucial to set clear objectives, use efficient educational strategies, and have dedicated, experienced surgeons to provide formative feedback.…”
Section: Availability Of Simulation Equipment In Vascular Surgerymentioning
confidence: 99%